Rare giant dermatofibrosarcoma protuberans with uncommon fibrosarcomatous transformation: case report and review of literature - Aggarwal, Manisha; Manchikanti, Dinesh; Misra, Sunayana; Thomas, Shaji; Arsia, Ashish; Pusuluri, Rahul; Kumar, Sanjay (International Surgery Journal, 2021)
Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue sarcoma with aggressive local behavior but with a low metastatic potential. Although slow growing and indolent, they rarely reach huge sizes. Very uncommonly, these locally invasive tumors undergo fibrosarcomatous transformation with a more aggressive clinical course, with higher rate of recurrence risk and distant metastases. A 32-years-old lady, presented with a gradually progressive lump in the upper central back for the past 6 years, with rapid progression in size during the last 6 months. On examination, she had a single lump of size 18×18 cm in the midline of the upper back, with prominent veins over its surface. Magnetic resonance imaging (MRI) showed no connection with the spinal canal and appeared flush with the paraspinal muscles. Core needle biopsy showed DFSP. The patient underwent a wide local excision with split skin grafting. The histopathology now showed a fibrosarcomatous transformation of DFSP. The patient again underwent a wide re-excision with a 3 cm margin. Histology reported no evidence of tumor cells in the specimen. The patient’s postoperative period was uneventful and she was referred for adjuvant radiotherapy. DFSP is a rare, slow-growing malignant fibroblastic mesenchymal skin tumor with low metastatic potential. However, in any patient with long standing DFSP with a recent increase in size, this fibrosarcomatous transformation must be kept in mind as it represents an uncommon form of DFSP that tends to follow a more aggressive clinical course, with higher rate of recurrence risk and distant metastases.